2016
DOI: 10.1016/j.pmpp.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid mitigates physiological and proteomic changes induced by the SPCP1 strain of Potato virus X in tomato plants

Abstract: a b s t r a c tInduction of resistance by salicylic acid (SA) exogenous treatment is a complementary approach to control plant diseases. SA effect on Potato virus X (SPCP1 strain) e infected tomato plants was examined by analyzing their physiological parameters and proteomic profiling at initial infection. PVX-SPCP1 altered photosynthesis and carbohydrate synthesis proteins and elicited stress proteins. SA partially offset reduction in photosynthetic rate during infection by increasing mesophyll conductance. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…The observations made in this work are in agreement with previous studies, which examined incompatible as well as compatible plant host-virus systems and demonstrated that induction of phytohormonal signaling could inhibit virus accumulation and/or movement and hamper virus host invasion [14,16,18,22,74,75]. Moreover, for tobacco mosaic virus (TMV) in tobacco, cucumber mosaic virus (CMV) in squash, and potato virus Y (PVY) in potato, virus accumulation in the inoculated leaves of a susceptible host was shown to be reduced upon the application of exogenous SA [18,76,77].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observations made in this work are in agreement with previous studies, which examined incompatible as well as compatible plant host-virus systems and demonstrated that induction of phytohormonal signaling could inhibit virus accumulation and/or movement and hamper virus host invasion [14,16,18,22,74,75]. Moreover, for tobacco mosaic virus (TMV) in tobacco, cucumber mosaic virus (CMV) in squash, and potato virus Y (PVY) in potato, virus accumulation in the inoculated leaves of a susceptible host was shown to be reduced upon the application of exogenous SA [18,76,77].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, for tobacco mosaic virus (TMV) in tobacco, cucumber mosaic virus (CMV) in squash, and potato virus Y (PVY) in potato, virus accumulation in the inoculated leaves of a susceptible host was shown to be reduced upon the application of exogenous SA [18,76,77]. Treatment with SA also had a profound effect on the cell-to-cell movement of TMV in N. benthamiana and tomato ringspot virus in tobacco and hindered the systemic translocation of TMV in N. benthamiana , CMV in tobacco and squash, and potato virus X (PVX) in tomato [14,15,16,18,75,78]. On the other hand, interfering with the SA pathways resulted in lowering the expression of corresponding PR genes and the increase of virus accumulation and systemic spread in the plum pox virus- n. tabacum , CMV-, turnip crinkle virus- or turnip mosaic virus- Arabidopsis , PVY-potato, and bamboo mosaic virus- or TMV- N. benthamiana pathosystems [74,76,79,80].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this evidence, it was proposed that SA plays a positive role in antiviral resistance by interfering with different steps of the viral cycle (Chivasa et al, 1997;Murphy and Carr, 2002;Alamillo et al, 2006). In addition, recent findings showed that SA treatment delays systemic movement of Potato virus X (PVX) (SCP1 strain) and ameliorates induced symptoms in tomato plants (Cueto-Ginzo et al, 2016). Thus, SA seems to play different roles in antiviral defence depending on the plant-viral pathosystem.…”
Section: Rna Interference-mediated Resistancementioning
confidence: 99%
“…Among the new forms of production are those aimed at compounds that may induce resistance to plants, such as salicylic acid (SA) (Monteiroet al, 2013). SA is a phenolic compound that occurs naturally in plants, playing an important role in regulating plant growth, development, maturation and defense responses (Almeida, 2012;Sánchez-Rangel et al,2015;Cueto-Ginzoa et al, 2016). In addition to the defense responses, SA acts in the response to abiotic stress, including drought, low temperature, salinity, among others.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the effect of SA on tomato plants (Solanumlycopersicum) infected with Tomato Potato (PV) X Virus (strain SPCP1) was examined by Cueto-Ginzoa (2016). According to the author, through the stabilization of photosystem II, SA partially compensated the reduction in the photosynthetic rate during the Abstract Background: Lettuce is grown and consumed practically all over the world, constituting an important source of minerals, especially calcium and vitamin A.…”
Section: Introductionmentioning
confidence: 99%